2021
DOI: 10.1136/bmjopen-2020-043480
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stroke early supported discharge on length of hospital stay: analysis from a national stroke registry

Abstract: ObjectiveThe first observational study to investigate the impact of early supported discharge (ESD) on length of hospital stay in real-world conditions.DesignUsing historical prospective Sentinel Stroke National Audit Programme (SSNAP) data (1 January 2013–31 December 2016) and multilevel modelling, cross-sectional (2015–2016; 30 791 patients nested within 55 hospitals) and repeated cross-sectional (2013–2014 vs 2015–2016; 49 266 patients nested within 41 hospitals) analyses were undertaken.SettingHospitals we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 23 publications
1
26
0
Order By: Relevance
“…23,38,72 Chapter 4 added to this debate by highlighting the importance of access to a social worker as part of the ESD team. 1 What was not possible to investigate in this study was whether or not access to ESD (despite an additional day in hospital) was associated with improved patient outcomes over the longer term. Recent observational studies in Sweden suggest patient and care-giver benefits related to the provision of ESD in regular clinical practice, in line with our previous study findings from England.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…23,38,72 Chapter 4 added to this debate by highlighting the importance of access to a social worker as part of the ESD team. 1 What was not possible to investigate in this study was whether or not access to ESD (despite an additional day in hospital) was associated with improved patient outcomes over the longer term. Recent observational studies in Sweden suggest patient and care-giver benefits related to the provision of ESD in regular clinical practice, in line with our previous study findings from England.…”
Section: Discussionmentioning
confidence: 89%
“…One important aspect of the ESD consensus score was to determine if a service meets the recommended WTE level of core staff per 100 patients. 1 Therefore, services that were resourced appropriately and had the adequate number of staff per patients were awarded a higher ESD consensus score. In this study, we found that it was the lower WTE amount of core staff per 100 patients within the most .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that resourcing a service that adheres to the core components of ESD service delivery requires costs to be appreciated on a per patient basis so that recommended staff to patient ratios are met. Our previous findings would suggest that further consequences of these additional cost implications may relate to additional patient benefit via the ESD service's ability to deliver a more responsive and intensive service [38].…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the consequence of higher service costs on a per patient basis was association with greater adherence to evidencebased core components, as measured by our ESD consensus score. One important aspect of the ESD consensus score was to determine if a service meets the recommended WTE level of core staff per 100 patients [38]. Hence, services that met the recommended number of staff per patients, were awarded a higher ESD consensus score.…”
Section: Discussionmentioning
confidence: 99%